The Relationship Of Hands Washing With The Event Of Diarrhea In Children Aged 7-8 Years Old In Class I SD Negeri 050685 Tanjung Selamat Kebun Jalan Besar Batang Sarangan, Padang Tualang TA. 2018/2019 - Ponidi Aswa; Srinur Nilawati; Ardianto; Andrianto; Sofyan; Risa Riyanti (Institute of Computer Science (IOCS), 2018)
This study aims to determine the relationship between hand washing and the incidence of diarrhea in children aged 7-8 years in Class I SD Negeri 050685 Tanjung Selamat Kebun Jalan Besar Batang Serangan, Padang Tualang District in 2018. The research method used to determine the relationship between hand washing and the incidence of diarrhea in Children aged 7-8 years is a descriptive correlative research using a cross sectional analytic study design. In this study, the sampling technique was carried out using a total sampling technique of 48 people. Based on the results of data analysis and discussion, it can be concluded that the majority of hand washing was carried out by 31 respondents (64.6%) and the minority was not carried out by 17 respondents (35.4%). The majority of the incidence of mild diarrhea were 24 respondents (50, 0%) and the heavy minority as many as 6 respondents (12.5%). The results of hypothesis testing to see the relationship between variable X and variable Y are with a significant level (α) = 5% (0.05) and df = 2, the results are p.value = 0.000 at df = 2 where sig < (0.000 < 0 0.05), it can be seen that there is a relationship between hand washing and the incidence of diarrhea in children aged 7-8 years in Class I SD Negeri 050685 Tanjung Selamat, Jalan Besar Batang Serangan, Padang Tualang District in 2018.